2019
DOI: 10.1101/748517
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Higher order interactions and coexistence theory

Abstract: 13Higher order interactions (HOIs) have been suggested to stabilize diverse ecological communities. 14 However, their role in maintaining species coexistence from the perspective of modern coexistence 15 theory is unknown. Here, using a three-species Lotka-Volterra model, we derive a general rule for species 16 42 or "rock-paper-scissors" interactions (Laird & Schamp, 2006; Gallien et al., 2017; Saavedra et al., 43 2017). Intransitive interactions are inherently pairwise in nature but they form intera… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Recent research has shown that non-linear or higher-order species interactions can affect community composition, community stability and coexistence (Grilli et al, 2017;Bairey et al, 2016;Mayfield & Stouffer, 2017;Singh & Baruah, 2019). We have shown, that niche and fitness differences can be used to understand why non-linear and higher-order species interactions affect community dynamics, however, our results remain limited to simple two-species communities.…”
Section: Future Directions Of Niche and Fitness Differencesmentioning
confidence: 81%
“…Recent research has shown that non-linear or higher-order species interactions can affect community composition, community stability and coexistence (Grilli et al, 2017;Bairey et al, 2016;Mayfield & Stouffer, 2017;Singh & Baruah, 2019). We have shown, that niche and fitness differences can be used to understand why non-linear and higher-order species interactions affect community dynamics, however, our results remain limited to simple two-species communities.…”
Section: Future Directions Of Niche and Fitness Differencesmentioning
confidence: 81%
“…Four-way or even higher-levels of HOIs, in which the interaction between two individuals is modified by two or more other individuals, are rarely considered in empirical studies (including ours) because of the huge number of parameters associated with them and the likelihood for diminishing returns on their inclusion. This is indeed the reason why these HOIs have only been explored theoretically [ 17 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ecologists have long hypothesized that these interaction modifications, or "Higher-order interactions" (HOIs), are a common phenomena in both competitive (Case and Bender, 1981;Worthen and Moore, 1991;Billick and Case, 1994;Wissinger and Jill, 1993;Mayfield and Stou er, 2017) and food web contexts (Morin et al, 1988;Wissinger and Jill, 1993;Paterson et al, 2015). But it has not been until recent years that researchers have systematically explored how these HOIs-mediated changes in per capita interactions modulate the dynamics and the functioning of ecological communities (Bairey et al, 2016;Grilli et al, 2017;Letten and Stou er, 2019;Kleinhesselink et al, 2019;Singh and Baruah, 2019;Li, Bearup, et al, 2020). To date, most e orts are theoretical, partly due to the di culty in gathering rigorous datasets to quantify HOIs.…”
Section: Introductionmentioning
confidence: 99%